Usborne Phonics Readers : Goat in a Boat - Sam Taplin (London, United Kingdom Usborne Publishing Ltd, 2015)
A lively story with humorous illustrations, ideal for children who are beginning to read for themselves, or for reading aloud together. With simple rhyming text and phonic repetition specially designed to develop essential language and early reading skills. Includes guidance notes for parents at the back of the book.
Keywords: PY - Language